Koordinasi Lintas Sektor dalam Percepatan Penurunan Stunting: Studi Kasus Implementasi Kebijakan di Kecamatan Pahandut, Kota Palangkaraya - Yustikarina Agustiani; Suryadi; Tjahjanulin Domai (Jurnal Bina Praja, 2025)
Stunting is a multidimensional issue whose management depends on cross-sectoral coordination. However, in Indonesia's regional bureaucracy, which is still influenced by patrimonialism, formal coordination is often ineffective, creating tensions between hierarchical policy design and the reality of decentralized implementation. This research uses a qualitative case study design in Pahandut District, Palangka Raya City. The location selection was based not only on the prevalence of stunting (20.8%) but also on its urban-rural hybrid characteristics, which offer an ideal setting for testing Winter's implementation model. Data were collected through in-depth interviews with nine key informants, participant observation, and document analysis, and were then analyzed thematically using triangulation. The stunting policy implementation was determined more by the agency of field actors and informal networks (e.g., WhatsApp groups) than by formal structures. Family Assistance Teams (TPK) acted as street-level bureaucrats, using discretionary resources such as local language use and context-based education to address system limitations. However, they faced minimal incentives and data fragmentation. The findings enrich Winter's model by introducing the concept of "informal governance resilience," the ability of a policy system to survive through informal mechanisms when formal governance fails. Recommendations include institutionalizing informal practices, providing appropriate incentives for TPK, and designing policies that are responsive to local structural barriers.